Perennial Water Stratification and the Role of Basal Freshwater Flow in the Mass Balance of the Ward Hunt Ice Shelf, Canadian High Arctic - Jefferies, Martin O. (1992)
A pronounced perennial water stratification in Disraeli Fjord behind the Ward Hunt Ice Shelf on the north coast of Ellesmere Island is described. 'ne ice shelf acts as a hanging dam at the mouth of the fjord and minimizes mixing between inflowing meltwater runoff and the seawater. Consequently, a 4 1 -m-deep layer of low salinity water, interposed between a 2- to 3-m-thick fjord surface ice layer and deeper seawater, is impounded behind the ice shelf. Highly negative delta 18O Values and high tritium activity in the low salinity water indicate it is derived primarily from snow-meltwater. Highly negative delta 18O values and high tritium values in a 5-m-thick basal ice layer in Hobson's Choice Ice Island, which broke off the East Ward Hunt Ice Shelf in 1982-83, might be evidence that basal accretion from freshwater flowing out of Disraeli Fjord below the ice shelf occurred prior to the calving. Using the known chronology of tritium occurrence in precipitation since 1952 and the measured levels in the basal ice, mean basal accretion rates of 96-141 mm yr-1 (water equivalent, w.e.) are calculated. The record of ablation and accumulation at the surface of the East Ward Hunt Ice Shelf for the period 1966-1982 shows an accumulated loss at the surface of 1.26 m (w.e.) at a mean annual rate of 74 mm yr-1. Therefore, despite many consecutive warm summers with considerable surface melting and runoff, the calculated basal accretion exceeds the surface loss and the ice shelf has increased, or at least maintained, its thickness. The thickening has been possible because of the feedback system created by the location of the ice shelf across the mouth of the fjord, the resultant water stratification and the outflow of freshwater below the ice shelf. This article is from 'Proceedings of the International Conference on the Role of whe Polar Regions in Global Change Held in Fairbanks, Alaska on 11-15 June 1990. Volume 1', AD-A253 027, p332-337. See also Volume 2, AD-A253 028.